2012 16th IEEE Mediterranean Electrotechnical Conference 2012
DOI: 10.1109/melcon.2012.6196450
|View full text |Cite
|
Sign up to set email alerts
|

Image processing of microscopic cellular samples

Abstract: This article presents image processing methods for biological Images which show kind of cells. The main difficulty of processing these images was the presence of noise in the images and the limitation of losing pixels during the binarization of the images. Neighborhood algorithm, such as the Wiener filter was used for noise removal. In addition to this, a normalization of the background was performed on the image before the binarization of the image and finally the application of morphological operations for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…For Transmission Electron Microscopy (TEM) images, several digital filters have been introduced by Kushwaha et al 7 such as median or Wiener filter. A similar work proposed by Sim et al 8 and Aguirre 9 based on employing an adaptive Wiener filter to enhance the effectiveness of the classical Wiener filter by considering the noise variance. Luisier et al 10 have suggested a Poisson Unbiased Risk Estimation-Linear Expansion of Thresholds (PURE-LET) technique for denoising images corrupted with Poisson noise.…”
Section: Introductionmentioning
confidence: 99%
“…For Transmission Electron Microscopy (TEM) images, several digital filters have been introduced by Kushwaha et al 7 such as median or Wiener filter. A similar work proposed by Sim et al 8 and Aguirre 9 based on employing an adaptive Wiener filter to enhance the effectiveness of the classical Wiener filter by considering the noise variance. Luisier et al 10 have suggested a Poisson Unbiased Risk Estimation-Linear Expansion of Thresholds (PURE-LET) technique for denoising images corrupted with Poisson noise.…”
Section: Introductionmentioning
confidence: 99%